Factors Influencing Turnaround Success in Financially Distressed Tourism, Hotel, and Restaurant Companies Listed on IDX (2020-2023) - Tresnajaya, Alyaa Rabbani; Tanzil, Nanny Dewi; Cempaka, Adisti Gilang (Universitas Padjadjaran, 2024)
The Covid-19 pandemic has significantly impacted business activities across various industries, leading many companies to face financial distress. Companies opting to continue their business operations may undergo corporate restructuring to sustain and reverse their performance (turnaround). This study aims to analyze the influence of management actions based on restructuring and economic conditions, including expense retrenchment, asset retrenchment, DER ratio, CEO turnover, and GDP, on the success of turnaround in companies experiencing financial distress, with free assets and firm size set as control variables. The Altman Z-Score model will be employed as a measurement of financial distress. This study's subjects are all 37 tourism, hotel, and restaurant companies consistently listed on the Indonesia Stock Exchange from 2020 to 2023. Sample selection utilized purposive sampling techniques, resulting in a sample size of 12 companies observed over three years. Logistic regression analysis will be used to test hypotheses. The research findings indicate that all independent variables positively influence turnaround success, but only expense retrenchment significantly impacts it.